DSDA: A DESIRABLE AND SECURE DEDUPLICATION APPROACH FOR OUTSOURCED DATA IN CLOUD ENVIRONMENT - Daniel, Esther; Susila, N.; Durga, S. (The journal of contemporary issues in business and government, 2021)
With ever-increasing and voluminous growth of data the enterprise cloud storage servers is critical since they provide efficient and desirable services to the end-users taking advantage of the cloud offerings in terms of providing services such as availability, reduced bandwidth, computational and storage cost. One of the solutions to provide low-cost storage services is Data Deduplication. This enables to save enormous storage space of the storage providers and thus reducing the cost. This paper proposes a deduplication technique termed Desirable and Secure Deduplication Approach for cloud storage environment (DSDA) eliminating duplicate data files and images securely. This approach combines convergent based encryption with a cuckoo filter to speed up the similarity search query and thus improves the performance while preserving the security. The experimental inference of this proposed approach exhibits reduced storage and communication cost.